The Application of Religious Tolerance Values in Salafiyyah Islamic Boarding Schools: A Case Study of Pesantren Al-Muthmainnah - Al Ghifari, Dzikri; Hermawan, Wawan; Nugraha, Risris Hari (AL-WIJDÃN Journal of Islamic Education Studies, 2025)
Religious tolerance is a fundamental value that sustains social harmony in a diverse society like Indonesia. Pesantren, particularly the Salafiyyah Al-Muthmainnah Islamic boarding school, as an educational institution emphasizing traditional Islamic teachings through the kitab kuning (classical Islamic texts), plays a strategic role in instilling the value of religious tolerance among its students to face the challenges of pluralism in society. Despite the absence of specific subjects on religious tolerance in the pesantren curriculum, students encounter the challenge of understanding how to implement tolerance in daily life. This issue makes it intriguing to explore how religious tolerance values are applied in this pesantren. This research examines the implementation of religious tolerance values in Pesantren Salafiyyah Al-Muthmainnah. Employing a descriptive qualitative research method, data were collected through direct observation and in-depth interviews with informants at the pesantren, using a triangulation approach. The analysis involved comparing observations and interviews, focusing on the learning processes, and applying religious tolerance values at Pesantren Salafiyyah Al-Muthmainnah. The findings reveal that Pesantren Al-Muthmainnah successfully implements religious tolerance values through the teaching of kitab kuning, wise instruction on differences in Islamic schools of thought (madhab), and community activities that reflect respect for diversity, both within the Muslim community and among followers of different religions. Therefore, despite its foundation in classical Islamic traditions, Pesantren Al-Muthmainnah serves as a solid platform for fostering religious tolerance values and significantly contributes to creating a harmonious society.   Keywords: Religius Tolerance, Pesantren Salafiyyah, Kitab Kuning